1992
DOI: 10.1042/bj2820645
|View full text |Cite
|
Sign up to set email alerts
|

The effect of protein kinase C activation on muscarinic-M3- and K+-evoked release of [3H]noradrenaline and increases in intracellular Ca2+ in human neuroblastoma SH-SY5Y cells

Abstract: Short-term pretreatment (9 min) with the phorbol ester 12-myristate 13-acetate (PMA) alone had no effect on the basal release of [3H]noradrenaline ([3H]NA), but enhanced K+ (100 mM)-, acetylcholine (0.1 mM)-, carbachol (1 mM)-, muscarine (I mM)-and arecoline (1 mM)-evoked release by 2.3-, 6.4-, 3.0-, 2.0-and 2.0-fold respectively in SH-SY5Y cells. the muscarinic-agonist-evoked initial peak (> 850%) and plateau phase in intracellular Ca2l. These results suggest that noradrenaline release evoked by muscarinic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 32 publications
4
13
1
Order By: Relevance
“…For example, activation of protein kinase C increased the amount of [3H]NOR released by muscarinic agonists (Murphy et al, 1992) and bradykinin (Luo and Weinstein, 1993) in SH-SY5Y neuroblastoma cells. Activation of protein kinase C also increased the amount of [3H]dopamine released by ionomycin in PC 12 cells sensitivity is that cells maintain their viability and exhibit many more functions than cell-free preparations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of protein kinase C increased the amount of [3H]NOR released by muscarinic agonists (Murphy et al, 1992) and bradykinin (Luo and Weinstein, 1993) in SH-SY5Y neuroblastoma cells. Activation of protein kinase C also increased the amount of [3H]dopamine released by ionomycin in PC 12 cells sensitivity is that cells maintain their viability and exhibit many more functions than cell-free preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the results of our recent studies on the TPA enhancement of NA release in SH-SY5Y cells (Murphy et al, 1992;Turner et al, 1994Turner et al, , 1996 and the results of the present study, a model for the role of PKC-a and MARCKS in the TPA enhancement of NA release can be constructed. Short-term treatment of cells with 100 nM TPA causes activation of the a and e subtypes of PKC, with PKC-a translocating from the cytosol to the plasma membrane within 6…”
Section: Marcks (Reviewed Bymentioning
confidence: 99%
“…The release of neurotransmitters by exocytosis from brain preparations (reviewed by Dekker et al, 1991), isolated nerve terminals (Nichols et al, 1987), and cultured neuronal cells (Matthies et al, 1987;Murphy et al. 1992) can be potentiated by short-term pretreatment with phorbol esters, which are potent activators of the protein kinase C (PKC) family of serine/threonine kinases (Nishizuka, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that muscarinic M3-receptor subtypes in SHSYSY are coupled to phosholipase C and IP3 induced changes in intracellular calcium [4,5]. Furthermore we have reported that activation of protein kinase C with TPA enhances both depolarisation and M3-receptor-evoked release of NA [6].…”
mentioning
confidence: 66%